Causal Economics: A new pluralist framework for behavioral economics that advances theoretical and applied foundations. Issue 4 (April 2019) - Horton, Andrew
Abstract: This paper introduces Causal Economics, a new pluralist framework for Behavioral Economics that allows for deep incorporation of psychological drivers at a level not possible in existing models. Its core theoretical breakthrough is the replacement of conventional single-value (net cost OR net benefit), single-period exogenous lottery outcomes as utilized within mainstream economics, with endogenous multi-period outcomes that always contain both personal total benefit (B) and personal total cost (C), including certain (deliberate) and uncertain components, with cause and effect running in at least one direction. Agents optimize an overall cumulative rank dependent weighted outcome value function against internal personal psychological trade-off constraints. Its core applied breakthrough is the introduction of the Causal Coefficient and four Causal Coupling Mechanisms to evaluate and guide development of effective economic and social activities, policies and institutions. Sustainable Pareto Optimal outcomes are predicted whenever causal coupling of B and C across involved or impacted agents is achieved via a Causal Coefficient ≥ 1. It provides a powerful pluralist framework for additional research into the optimality of concepts that prioritize individual freedom of choice and responsibility to society.